EVALUASI IMPLEMENTASI PROSEDUR PENGELOLAAN BARANG MASUK DAN KELUAR PADA WAREHOUSE DI PT PATRIA LINTAS JAYA - Raisya Anjar Nurhidayah; Tuti Wediawati (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aims to evaluate the implementation of incoming and outgoing goods management procedures in the warehouse at PT Patria Lintas Jaya. The research method used was a qualitative approach, with data collection techniques through in-depth interviews with the Warehouse Head. The results indicate a discrepancy between standard operating procedures and field practices, particularly in the inventory recording and control process. The main obstacles identified include limited human resources in administration, a suboptimal semi-manual recording system, and a lack of regular monitoring of procedure implementation. These conditions result in discrepancies in stock data, resulting in a lack of synchronization between physical records and the system. Therefore, improvements are needed through digitalization of the inventory system, additional administrative staff, and increased compliance with established procedures to ensure more effective and efficient warehouse operations.